RESULTS OF TREATMENT OF GLIAL BRAIN TUMORS - R.G. ASHUROV; E.A. KOROTKEVICH; R.R. SIDOROVICH (Паёми Сино, 2017)
Objective: To improve the treatment results of patients with brain glioma of varying degrees of malignancy by improving post-operative diagnostics and surgical tactics.